2022
DOI: 10.1037/sgd0000515
|View full text |Cite
|
Sign up to set email alerts
|

“I’m still not sure if the eating disorder is a result of gender dysphoria”: Trans and nonbinary individuals’ descriptions of their eating and body concerns in relation to their gender.

Abstract: Conceptualizations of eating disorders (ED) have primarily been based on the experiences of cisgender women. Yet trans and nonbinary individuals (TNB) may be at greater risk than cisgender individuals to suffer from eating disorders, disordered eating, and body image concerns. The current study takes a phenomenological approach to explore how TNB individuals conceptualize eating and/or body image issues. Qualitative data were obtained from 82 TNB participants who self-reported eating and/or body image concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 87 publications
1
27
0
Order By: Relevance
“…binary gender expression, such as masculinity or femininity. 43 Such excessive body concerns probably put them at suicide-related risk. 22 Second, a queer theory framework suggests that stereotypical gender expectations in a cultural context can exacerbate young TGD adults' worries about their appearance and may contribute to body dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…binary gender expression, such as masculinity or femininity. 43 Such excessive body concerns probably put them at suicide-related risk. 22 Second, a queer theory framework suggests that stereotypical gender expectations in a cultural context can exacerbate young TGD adults' worries about their appearance and may contribute to body dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In this data set, being an ethnic minority, low on socioeconomic status, overweight or older in age may pose additional challenges to the gender affirmation journey. Research has shown that these identifiers often carry with them their own stigma and otherness and, therefore, can cause additional negative stress for the TGD individual (Garthe et al , 2020; Hernandez, 2020; Lazaro and Bacio, 2021; Lee et al , 2021; Cusack et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…and gender diverse consumers their own stigma and otherness and, therefore, can cause additional negative stress for the TGD individual (Garthe et al, 2020;Hernandez, 2020;Lazaro and Bacio, 2021;Lee et al, 2021;Cusack et al, 2022).…”
Section: Transgendermentioning
confidence: 99%
“…Thus, while the results from our community sample of higher weight SMW provide a helpful starting point, these findings may not necessarily generalize to clinical populations or other sexual and/or gender minority populations. For example, transgender females are likely to have unique experiences at the intersection of weight, body image, and stigma relative to cisfemale SMW (e.g., Cusack et al, 2022), and research investigating weight stigma among gender-expansive and transgender individuals is an important future direction.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%